Islamic Teachings on Quality Assurance in Islamic Education - Ulfah, Maria; Suharyat, Yayat (MultiTech Publisher, 2023)
This paper describes the teachings of Islam in ensuring the quality of Islamic education. Based on the content in Qs. Ar-Ra'du verse 11 which reads: